Estudio comparativo de las unidades básicas de saneamiento de arrastre hidráulico con biodigestor y sanitario ecológico seco en el caserío de retambo, distrito de Quiruvilca, Santiago De Chuco - Moreno Alipio, Jossy Fiorella (2019)
In this research presents the comparative study of two technological options for the sanitary disposal of excreta, the basic unit for sanitary drainage with biodegester and dry ecological sanitary on the village of Retambo, district of Quiruvilca, Santiago de Chuco – La Libertad. This village is conformed by 46 houses which are too distant from each other, that’s why the projection of a conventional sanitary system becomes difficult to realize, on the other hand, there are other unconventional technologies that allow us to provide all the basic needs of sanitation in rural zones. Previous studies were made for the selection of these options, previous studies were carried out such as the topographic survey of the area, the soil study and the percolation test for the technical definition of the aspects in the design of these units, the design criteria applied in this thesis were bases on the “Ministerio de Vivienda, Construcción y Saneamiento”. As a result plans, measures and finally the budget were obtained for the construction of the basic units of the sanitary system in the village of Retambo. An investment of S/. 727,786.13 for the basic units of hydraulic drag, biodigester and absorption for 46 basic units with a duration of 60 calendar days for the construction and implementation, while for the basic unit of composting sanitary system with wetland the investment is S/. 1,638,852.48 for 46 units with a duration of 90 calendar days for its building and implementation.